السبب المبيح لأعمال الطبيب في الفقه والقانون (مجلة الواحات للبحوث والدراسات, 2015)
Early Muslims and others interested inMedicine career and they gave it a great care, so they gave it the honor to be the greatest occupation and profession that we must learn, teach, practice and performed to the people. Muslims are the first who built specialized hospitals for disabled and maniacs; due to the Islam’s perception which consider them as patients and irresponsible for actions. The reason for allowing illicit businesses in law according to Britain’s scholars’ doctrine is the acceptance of patient already, also some scholars in Germany and France took this way, and courts in old France and Egypt. Many of French’s scholars said that the reason for being highly responsible is the absence of criminal intent; because the doctor does what he does to heal the patient, the Egyptian jurists took this way of thinking for some time. Now, the latest opinion and view which prevails in Egypt and France is that medication is a social necessity cannot be ignored at all. And it is a legal profession enacted, organized and supported by the government; due to the social life exigency and demand. Those reasons (even they are various) are the same reasons which made and considered by Muslims scholars and jurists that the doctor is totally exempt from any responsibility if his work conduct to detrimental results to patient. You can notice from this article that the reason of allowing doctor’s illicit actions is already available in criminalization reason which is right and benefit’ protection. And there is no conviction about doctor’s action with patient or sponsor acceptance, also there is no conviction when there wasn’t a criminal intent. As the thing that considered a social life exigency is considered also as an exigency do not criminalized. And all aims to achieve and protect a right or a benefit. So, it can be to collect all reasons and the consideration is by its collection, which are: 1-social exigency 2-patient or sponsor’s permission 3-the ruler’s permission 4-the good intent of doctor to save and not to damage the patient.And we saw that the law is compatible with "Shareyaa" in the same reason of allowing doctor’s illicit actions which is to protect a right and a benefit. The terms oftaking off the criminalization’s responsibility from practicing medical work and actions in law are: 1-specializing in profession. 2-taking patient treatment approval. 3-achieving the purpose: which is treating and healing the patient not doing a scientific experiment on him/her. 4-folowing the profession art’s rules